Establishment of thermal process for chili garlic shrimp sauce - Mamalio, Christine Dorothy L.; Cornago, Djanna F. (2009.)
ABSTRACT The study established the thermal process for Chili Garlic Shrimp Sauce. Water activity and pH of the sample prior to processing were determined and returned the values of 0.791±0.002 and 6.32±0.18, respectively. These values were used as basis for the reference microorganism and the time-temperature process protocol of 228°F for 30 minutes. Heat penetration studies were done to establish the lethality of the thermal process. Cut-out tests and microbiological, physico-chemical and sensory analyses of the sample were conducted after processing. The post processing pH of 6.47±0.20 was higher than those obtained by other studies, while the water activity value of 0.792±0.018 was lower. The process gave a lethality of 0.71±0.16, which is within the range of the required F0 value for the reference microorganism, Clostridium sporogenes. Therefore, the thermal process is considered adequate. This was confirmed by microbiological examination which showed negative results for mesophilic and thermophilic microorganisms that could be present in the sample after processing. Sensory evaluation showed a mean acceptance ranking of 7.20±1.16 for color, 7.23±1.57 for aroma, 7.06±1.51 for flavor, 7.00±1.178 for saltiness, 7.40±1.29 for spiciness, and 7.29±1.23 for over-all quality, signifying that the product was moderately liked based on all parameters evaluated.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Sauces; Shrimp sauce -- Processing